Biochemical, biophysical, and functional properties of ICA512/IA-2 RESP18 homology domain - Sosa, Laura (2016)
Background ICA512 (or IA-2/PTPRN) is a transmembrane protein-tyrosine phosphatase located in secretory granules of neuroendocrine cells. Previous studies implied its involvement in generation, cargo storage, traffic, exocytosis and recycling of insulin secretory granules, as well as in β-cell proliferation. While several ICA512 domains have been characterized, the function and structure of a large portion of its N-terminal extracellular (or lumenal) region are unknown. Here, we report a biophysical, biochemical, and functional characterization of ICA512-RESP18HD, a domain comprising residues 35 to 131 and homologous to regulated endocrine-specific protein 18 (RESP18). Methods Pure recombinant ICA512-RESP18HD was characterized by CD and fluorescence. Its binding to insulin and proinsulin was characterized by ELISA, surface plasmon resonance, and fluorescence anisotropy. Thiol reactivity was measured kinetically. Targeting of ΔRESP18HD ICA512-GFP to the membrane of insulinoma cells was monitored by immunofluorescence. Results ICA512-RESP18HD possesses a strong tendency to aggregate and polymerize via intermolecular disulfide formation, particularly at pH > 4.5. Its cysteine residues are highly susceptible to oxidation forming an intramolecular disulfide between cysteine 53 and 62 and intermolecular disulfides via cysteine 40 and cysteine 47. The regulated sorting of ICA512 to secretory granules in INS-1 cells was impaired by deletion of RESP18HD. ICA512-RESP18HD binds with high-affinity to insulin and proinsulin. Conclusions RESP18HD is required for efficient sorting of ICA512 to secretory granules. General significance RESP18HD is a key determinant for ICA512 granule targeting.